THE EFFECT OF E-LEARNING ON CHARACTER BUILDING: PROPOSITION FOR ORGANIZATIONAL BEHAVIOR COURSE - Setyabudi Indartono (Jurnal Pendidikan Karakter, 2011)
Abstract: Phenomenon of character as well as human behavior becomes more attractive through education prosess within E-learning. Scholars have attempted to investigate various attitudes and behaviors of the students during learning processes. However, few scholars explore the character building of students who are taking a course of organizational behaviors, whereas the course containing behaviors shapes students character. Hence this study proposes the integrated learning process of human behavior in order to shape the character of the student, including the effect of integrated and simultaneous processes of education on character, and support of E-Learning on the character education and through delivering course of organizational behavior. Limitation and future research direction are discussed. Keywords: E-Learning, character building, organizational behavior